Letting go : the story of Zen Master Tōsui : Tōsui oshō denshan - Menzan Zuihō, 1683-1769 (University of Hawaiʼi Press, 2001)
Of the many eccentric figures in Japanese Zen, the Soto Zen master Tosui Unkei (d. 1683) is surely among the most colorful and extreme. Variously compared to Ryokan and Francis of Assisi, Tosui has been called "the original hippie." After many grueling years of Zen study and the sanction of a distinguished teacher, Tosui abandoned the religious establishment and became a drifter. The arresting details of Tosui's life were recorded in the Tribute (Tosui osho densan), a lively and colloquial account written by the celebrated scholar and Soto Zen master Menzan Zuiho. Menzan concentrates on Tosui's years as a beggar and laborer, recounting episodes from an unorthodox life while at the same time opening a new window on seventeenth-century Japan. The Tribute is translated here for the first time, accompanied by woodblock prints commissioned for the original 1768 edition. Peter Haskel's introduction places Tosui in the context of the Japanese Zen of his period--a time when the identities of early modern Zen schools were still being formed and a period of spiritual crisis for many distinguished monks who believed that the authentic Zen transmission had long ceased to exist. A biographical addendum offers a detailed overview of Tosui's life in light of surviving premodern sources